COFFEEHOUSE PAINTING: ART, FAITH, AND SOCIETY - Rahiminejat, Rahim (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Coffeehouse (Qahveh-Khaneh) painting, a vibrant Iranian folk art form flourishing during the Qajar era (18th-20th centuries), has been primarily studied through its aesthetic or sociological aspects. This research uniquely investigates its multimedia nature, revealing a dynamic interplay with the oral storytelling tradition of Naqqali and the theatrical performances of Ta'zieh. To analyze the historical development, artistic characteristics, social functions, and cultural impact of Coffeehouse painting within the Iranian context, highlighting its multimedia character and its relationship with Naqqali and Ta'zieh. A qualitative thematic analysis of existing scholarly literature, predominantly in Persian, was conducted. Sources were reviewed, translated, and analyzed to identify recurring themes and patterns. Coffeehouse paintings served as a powerful medium for disseminating religious beliefs, shaping national identity, and bolstering morale during a period of colonial influence. The art form's visual conventions and narrative strategies were deeply intertwined with Naqqali and Ta'zieh traditions. This study reveals Coffeehousepain ting as a significant force in shaping Iranian cultural identity and underscores the importance of studying multimedia art forms within their specific socio-historical contexts.